Edukasi Manfaat Olahraga Terstruktur Bagi Pembentukan Karakter 5C Anak Pada Orang Tua Murid Humble Basketball Academy di Kota Surakarta - Syaukani, Agam Akhmad; Sanggita, Mohammad; Rahman, Aulia (Jurnal Pengabdian UNDIKMA, 2022)
The purpose of this community service program is to provide an understanding of the benefits of structured exercise for children. This program is intended for parents of students at Humble Basketball Academy Surakarta City, Central Java. The respondents to this activity were 40 people. The community service program is carried out by interactive discussion, question and answer, and evaluation methods. The results of the activity showed that parents get useful information related to the potential of children that can be developed from their participation in the basketball academy. Through this activity parents realize the benefits obtained by children through structured sports activities not only limited to physical health and motor development, but also emotional maturity and social intelligence through practice of 5C’s characters. The community service program is expected to assist Humble Basketball Academy managers in convincing parents about the benefits of child development through sports activities reviewed from academic studies.